La equidad de género en la educación física - Molina Tapia, José Luis (2016)
The purpose of this project is to diagnose the equity degree of gender that exists in physical education classes, using the indirect method, the technique of observation and instruments such as, chips observation was also used and identify the direct problem the causative agent of unfairness in children, when running group, individual activities, integration, collective or gender specific games, is intended to correct this problem of inequality, traditionalist education in sport and gender difference, aside equal opportunities in infants holding back the development of good quality education and warmth with equal opportunities for all, once the problem or the causative agents of the same identified after analyzing the results data obtained a guide specific activities will be proposed to enhance gender equality with new activities such as traditional games, aimed at promoting gender equality, workshops which will run for parents and students teachers of the Education Unit Victoria Vasnonez Cuvi, an impact on the educational-field Physical Culture and training of students bailing integrates essential values for the good development of education and integration will. The result is that children (as) have the same opportunities in physical education classes promoting respect and instilling new values that will help them in the course of his entire life.